A Known and a Novel Mutation in the Glycine Decarboxylase Gene in a Newborn with Classic Nonketotic Hyperglycinemia - Beijer, P.; Lichtenbelt, K.D.; Hofstede, F.C.; Nikkels, P.G.J; Lemmers, P.; de Vries, L.S. (Neuropediatrics, 2012)
A term neonate displayed typical features of nonketotic hyperglycinemia (NKH). Conventional magnetic resonance imaging showed corpus callosum hypoplasia and increased signal intensity of the white matter. Magnetic resonance proton spectroscopy revealed high cerebral glycine levels. The liquor/plasma glycine ratio was increased. Genetic testing detected a known and a novel mutation in the glycine decarboxylase gene, leading to the classic form of glycine encephalopathy. Prenatal genetic testing in the subsequent pregnancy showed that this fetus was not affected. As features of neonatal NKH may not be very specific, recognition of the disease may be difficult. An overview of clinical, electroencephalography, and neuroimaging findings is given in this article.
Keywords: newborn; nonketotic hyperglycinemia; mutation